Further investigations on IR-RF: Dose recovery and correction. (15th December 2018) - Murari, Madhav Krishna; Kreutzer, Sebastian; Fuchs, Markus
Abstract: We discuss the dose recovery behaviour of IR-RF from K-rich feldspar extracts from modern-analogue sediment samples. The zero-dose of these samples was confirmed from previous quartz OSL and feldspar IRSL measurements. In our experiments, the IR-RF curve (RFnat ) from the naturally bleached sample was taken as a regenerated curve within dose recovery experiment. We report that the obtained dose varies by 15% to 23% from the given dose, when recovered from naturally bleached IR-RF curves. However, it matches with the IR-RF regenerated (RFreg ) curve bleached with a solar simulator. We discuss the potential reasons for the observed differences and present two correction methods: background subtraction and vertical curve sliding. We conclude that a given dose can be successfully recovered up to 3, 600 Gy if the vertical sliding method is applied. Our results further indicate that an applied signal correction by vertical sliding improves the overall accuracy of IR-RF dose estimations. The incorrect dose recovery of naturally bleached samples without signal correction implies that the estimated palaeodoses from natural samples may not be reliably reconstructed if no correction is applied. Highlights: Investigation of IR-RF dose recovery behaviour of K-feldspar. Newly proposed methods, background subtraction, and vertical curve sliding. Both correction methods are able to recover doses within the uncertainty of 10%. Vertical curve sliding method minimizes machine measurement time significantly. High laboratory dose up to 3600 Gy can be recovered using correction method.